A Bibliometric Analysis of E-Learning Research Trends - Regina Deti; Virginia Mandasari (International Journal of Theory and Application in Elementary and Secondary School Education, 2021)
The teaching and learning process as if there must always be an increase in effectiveness in order to achieve the goals to be achieved. The development of the world of information technology has now become so fast and has penetrated various sides of human life. The use of information technology such as e-learning, one of which is through web-based learning, will bring significant changes both in terms of the education system to be developed, the material to be delivered, how the instructional and learning processes will be carried out, and the obstacles that will be faced either by the education recipient and the educators. This research uses bibliometric analysis to map how e-learning is intended from several previous journals using vosviewer. This research concludes that e-learning is unavoidable, especially in the industrial era 4.0, where e-learning is believed that education can be accessed anytime, anywhere, and by anyone.